2002
DOI: 10.5194/angeo-20-691-2002
|View full text |Cite
|
Sign up to set email alerts
|

The 16-day planetary waves: multi-MF radar observations from the arctic to equator and comparisons with the HRDI measurements and the GSWM modelling results

Abstract: Abstract. The mesospheric and lower thermospheric (MLT) winds (60–100 km) obtained by multiple MF radars, located from the arctic to equator at Tromsø (70° N, 19° E), Saskatoon (52° N, 107° W), London (43° N, 81° W), Hawaii (21° N, 157° W) and Christmas Island (2° N, 157° W), respectively, are used to study the planetary-scale 16-day waves. Based on the simultaneous observations (1993/1994), the variabilities of the wave amplitudes, periods and phases are derived. At mid- and high-latitude locations the 16-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
94
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(122 citation statements)
references
References 47 publications
23
94
1
Order By: Relevance
“…There is also an oscillation of period ∼16 days and amplitudes of order ∼15 m s −1 and 10 K in December and January, similarly marked on the figure. These periods are consistent with those reported for the "5-day wave" and the "16-day wave", respectively (e.g., Espy and Witt, 1996;Espy et al, 1997;Luo et al, 2002b;Lieberman et al, 2003;Riggin et al, 2006;Day and Mitchell, 2010a,b;Day et al, 2011).…”
Section: -And 5-day Planetary Wavessupporting
confidence: 80%
“…There is also an oscillation of period ∼16 days and amplitudes of order ∼15 m s −1 and 10 K in December and January, similarly marked on the figure. These periods are consistent with those reported for the "5-day wave" and the "16-day wave", respectively (e.g., Espy and Witt, 1996;Espy et al, 1997;Luo et al, 2002b;Lieberman et al, 2003;Riggin et al, 2006;Day and Mitchell, 2010a,b;Day et al, 2011).…”
Section: -And 5-day Planetary Wavessupporting
confidence: 80%
“…The theoretical expectation for this wave is for propagation from the lower atmosphere and resulting activity throughout the winter hemisphere's eastward flow, with the possibility of summer mesopause activity due to propagation from the winter hemisphere. The results from the 2-D Global Scale Wave Model (GSWM) in Luo et al, (2000Luo et al, ( , 2002b were generally consistent with this simple scenario, but also demonstrated strong sensitivity to the background winds in the model. Our observations reinforce those conclusions: we again hypothesize that local conditions (winds, other PW modes, PW and GW interactions, and temperatures) may favour responses or resonances of different amplitude and at different periods at different sites.…”
Section: -D Pwsupporting
confidence: 51%
“…For example, the observed zonal/EW wind's ∼10 d oscillation (taken to be the regional response to a Rossby PW) near day 30, is also evident in the NS component. The NS component is typically weaker in a Rossby wave (Luo et al, 2002). However, the feature in the contours near 10 d in the zonal-CMAM wavelet is less coherent and convincing, while it is not present in the meridional-wavelet.…”
Section: High-arctic Frequency Spectra (Wavelets)mentioning
confidence: 92%